A model of holistic personality based on transformative educational approach - Rahimah, Embong; Normila, Noruddin@Che Ahmad; Norsuhaily, Abu Bakar; Azhar, Yaacob; Nik Murshidah, Nik Din; Raja Hazirah, Raja Sulaiman (2015)
This paper aims to propose a model of holistic personality which is designed by using transformative educational approach. Initially, it will discuss on the issue of dual personality which creates dilemma facing the humankind resulted from the rapid changes brought by globalization and its impacts. Then, the characteristic and indicators of holistic personality from a transformative educational approach will be elucidated in order to develop a model of personality. Finally, some implications of this proposed model of holistic personality will be discussed. The world today witnesses numerous problems such as corruption, oppression, depression, and aggression. These phenomena are infecting even those highly educated people throughout the world including Eastern and Western countries. The existing systems of education seem facing failure in developing a good personality of man. The modern system of education was seemingly has high value but producing alienated individuals whereas the traditional system of education tends to be neglected and thus, producing unproductive individuals. Their products have opposing world-views, lifestyles and personalities. This issue becomes a major concern for contemporary scholars, certain efforts could be taken such as; construct a set of universal ethical system with the universality of religion as the way of life for all mankind and its value centered system of education could cause a global paradigm shift and educational change. This effort requires the elaboration of universal and core values and their significances on cultural and social system. Hence, there is an urgent need to develop an individual with a holistic personality. As a consequence, the system of education and its approach should be transformed to be more holistic. This transformative education should ensure the cumulative effect of the whole set of programmes will prepare the young generation with a strong personality to face the challenges in the twenty-first century. This conceptual research focuses on developing a theory to design a model of holistic personality. It involves the integration of three domains of research processes namely conceptual, methodological and substantive. It is hoped that its findings will benefit educators, academics, counsellors and parents for developing personality of a person.